Digital Economy Regulation and Consumer Rights Protection: Realizing Security in Financial Technology Transactions - Afif Noor; Ali Maskur; Dwi Wulandari; Aqila-Syarief Muhammad Afif; Muhammad Fazli Azmi (Lex Scientia Law Review, 2025)
Financial technology has experienced rapid expansion amidst the digital economic development that has made services more accessible while increasing financial inclusion. The rapid growth of financial technology creates substantial challenges for consumer protection. The primary problems arise from inadequate data protection measures and electronic payment security protocols. The lack of proper security measures and insufficient digital literacy exposes consumers to increasing risks of data theft, phishing attacks, and personal information misuse. This research evaluates the current regulatory structure that defends consumer rights and ensures secure financial operations through technological systems. The study adopts a normative legal research method through statutory analysis. The research shows that Indonesia's regulatory framework extends broad protection but requires modernization to address contemporary technological developments and emerging security risks. Fintech requires a regulatory framework that adjusts to evolving conditions while fostering partnerships to deliver adequate consumer protection.